Pemanfaatan Simplex Noise Untuk Menghasilkan Map Yang Natural dengan Unity Engine - Calvin Vionaldy Tjiandra; Rudy Adipranata; Lily Puspa Dewi (Jurnal Infra, 2021)
In the development of game, terrain is the first thing that theplayer see in the game. Landscape, assets on terrain, and theheight kurvator on the terrain will give an environment that canenhance the experience in playing. But the process of making suchterrain will take a long time because of the terrain setting whichdevelopers do. Moreover, if the developer needs to create manyterrain with a similar parameter. not just that, because thesimilarity from the terrain, the terrain itself will becomerepetitive. To avoid that, it is better to use the Procedural ContentGenerator or PCG to create a base terrain with every project.Simplex noise is one of many PCG method to generate a terrainheight map to be developed by developer. Terrain that had beengenerated can be explore by the player , and to diminish thechance of slump because of the repetitive play, the surface will bedifferent each time the method generate.This paper will be focus on the implementation of simplex noise togenerate a base terran for a 3D game with the usage of C# fromunity. simplex noise will generate 3 biomes which are the forest,savanna, mountain. Perlin noise will be implemented as well forthe purpose of comparison method, perlin noise will generate thesame biome as simplex noise. This program will see the result ofthe surface generated by both methods.This paper will test some terrain models by how the result ofsimplex generated terrain and perlin generated terrain can makea variety for terrain. Terrain will change each time the method isrunning in the program. In the result of the paper, it is found thatperlin have an advantage to generate that have a low to middleheight terrain and simplex have the advantage to generate aterrain that have a middle to high height.